Effect of tryptophan enriched diets on aggression in hierarchical groups of juvenile Atlantic salmon (Salmo salar) - Vindas Alvarado, Marco Antonio (The University of Bergen, 2010)
Aggression in fish hierarchies often leads to one dominant individual monopolizing resources (food/shelter), thus increasing their fitness. Meanwhile individuals in subordinate ranks, endure high stressful conditions, which often lead to disease and higher mortality rates. Levels of serotonin have been linked to agonistic behavior. Enriching fish diets with tryptophan (TRP), the natural precursor for serotonin, has been used in several vertebrate species in order to control aggression levels. Twelve hierarchies consisting of 4 fish in each were studied. Six groups were given a TRP enriched diet and six groups a control diet. Aggressive acts performed and those received were observed during 7 days, 15 min per day, in order to establish hierarchies. Whole brains were excised and immediately frozen from each fish at the end of the trial, in order to analyze the monoamine levels by means of HPLC chromatography. TRP groups were found to have a higher overall aggression compared to control groups. Dividing the groups into their hierarchical ranks, middle rank individuals were overall more aggressive, displaying also more aggressive attacks towards dominants in TRP groups, compared with control groups. These results were opposite to what was expected. Serotonergic activity, measured as the [5-HIAA]/ [5HT] ratio, was higher in more aggressive individuals, which is also opposite from what has been found before. High amounts of received aggression were found to be positively correlated with high [5-HIAA]/ [5HT] ratios. This is the first time (as far as we know) that the effect of a TRP enriched diet on fish hierarchical groups has been studied. Our contradictory results show how complicated the social interactions and mechanisms in fish hierarchies are, since previous studies have only looked at fish interacting in pair-wise contests. We propose that under true hierarchical conditions, other factors are involved in the overall control of aggression; therefore, attempting to control agonistic behavior in groups of fish ...